Microstructural evolution of aluminum alloy during friction stir welding under different tool rotation rates and cooling conditions. Issue 6 (June 2019) - Zeng, X.H.; Xue, P.; Wu, L.H.; Ni, D.R.; Xiao, B.L.; Wang, K.S.; Ma, Z.Y.
Highlights: A DRX mechanism of progressive lattice rotation associated with the pinning of the second-phase particles was the first time proposed. A universal conclusion of microstructural evolution along material flow based on different FSW parameters was observed. The relationship of DRX mechanisms (and grain morphologies) vs the Zener-Hollomon parameter related to welding parameters was clarified. Further dislocation multiplication after DRV provided driving force for DRX during FSW; the delay of DRV/DRX efficiently refined the grains. Ultra-high strain rate and short durations at high temperatures were the key factors to produce an ultrafine-grained material. Abstract: The microstructural evolution during friction stir welding (FSW) has long been studied only using one single welding parameter. Conclusions were usually made based on the final microstructure observation and hence were one-sided. In this study, we used the "take-action" technique to freeze the microstructure of an Al-Mg-Si alloy during FSW, and then systematically investigated the microstructures along the material flow path under different tool rotation rates and cooling conditions. A universal characteristic of the microstructural evolution including four stages was identified, i.e. dynamic recovery (DRV), dislocation multiplication, new grain formation and grain growth. However, the dynamic recrystallization (DRX) mechanisms in FSW depended on the welding condition. For the air cooling condition, the DRX mechanisms were related to continuous DRX associated with subgrain rotation and geometric DRX at high and low rotation rates, respectively. Under the water cooling condition, we found a new DRX mechanism associated with the progressive lattice rotation resulting from the pinning of the second-phase particles. Based on the analyses of the influencing factors of grain refinement, it was clearly demonstrated that the delay of DRV and DRX was the efficient method to refine the grains during FSW. Besides, ultra-high strain rate and a short duration at high temperatures were the key factors to produce an ultrafine-grained material.